Thermal Evaluation of Indoor Climate and Energy Storage in Buildings - Shailendra Kumar Shukla (CRC Press, 2024)
There is a need to reduce energy consumption for space cooling and heating via energy efficient solutions/technologies for implementation in the buildings. Thermal energy storage regulates indoor temperature, shifting the peak load to the off-peak hours and reducing the energy need for space cooling and heating. This book presents the most recent advances related to the thermal energy storage system design and integration in buildings. Additionally, modelling, application, synthetization, and characterization of energy efficient building materials are also considered.Features: Provides a deep understanding of thermal energy storage technology and summarizes its utility and feasibility that can be commercially implemented worldwide Covers recent advancements related to thermal energy storage system design and integration in buildings Discusses modelling, application, synthetization, and characterization of energy-efficient building materials Details novel and emerging heat storage materials and their application to energy and environmental processes Highlights the need for future research on building comfort in cooling, heating, and ventilation through a green energy perspective This book is aimed at researchers and graduate students in mechanical, renewable energy, and HVAC engineering.